2013
DOI: 10.1007/s10508-013-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

A Treatment-Oriented Typology of Self-Identified Hypersexuality Referrals

Abstract: Men and women have been seeking professional assistance to help control hypersexual urges and behaviors since the nineteenth century. Despite that the literature emphasizes that cases of hypersexuality are highly diverse with regard to clinical presentation and comorbid features, the major models for understanding and treating hypersexuality employ a “one size fits all” approach. That is, rather than identify which problematic behaviors might respond best to which interventions, existing approaches presume or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 24 publications
0
30
0
3
Order By: Relevance
“…The number of boys was significantly higher in the adolescents with high levels of CSB and among sexual fantasizers than among sexual abstainers. Previous studies have indicated that one possible reason for that is that boys are more likely to be sexually active, and that adolescent boys were found to have a higher level of sexual arousal than girls [67, 68]. …”
Section: Discussionmentioning
confidence: 99%
“…The number of boys was significantly higher in the adolescents with high levels of CSB and among sexual fantasizers than among sexual abstainers. Previous studies have indicated that one possible reason for that is that boys are more likely to be sexually active, and that adolescent boys were found to have a higher level of sexual arousal than girls [67, 68]. …”
Section: Discussionmentioning
confidence: 99%
“…Future research is needed to fine tune the construct of hypersexuality, which may be a manifestation of a number of etiological and mechanistic pathways, including impulse control, affect management, or compulsive behavior. Differences in clinical presentation have been found (57), which may provide useful sub-types for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Tercera etapa Segunda etapa Primera etapa Carnes (1983) Kafka (1997) Cantor et al (2013) Kafka (2010) Coleman (1992) Coleman et al(2003) 6. Clasificación de la conducta sexual compulsiva…”
Section: La Segunda Sería La Escala De Consecuencias Cognitivas Y Conunclassified
“…De igual modo que no todos los pacientes con CS comparten los mismos síntomas, sus manifestaciones pueden ser muy diferentes. De ahí su consideración de fenómeno único expresado a través de múltiples formas (Cantor et al, 2013).…”
Section: La Segunda Sería La Escala De Consecuencias Cognitivas Y Conunclassified
See 1 more Smart Citation